Histological characterization of the digestive system in larvae of the pez Capitán de la Sabana, Eremophilus mutisii - Moncaleano Gómez, Erika Marcela (2025)
The Capitan de la sabana fish (Eremophilus mutisii) is an endemic species of the Colombian Cundiboyacense plateau with high potential for aquaculture, although it is currently in a vulnerable state. The study aimed to describe the development of the digestive system during the early stages of life to optimize captive breeding strategies and contributing to its conservation. Larvae were obtained by artificial insemination and evaluated at three developmental stages: early (EF), middle (MF), and final (FF). Specimens were euthanized with an overdose of tricaine methanesulfonate, fixed in 4% formalin, and histological slides were stained with haematoxylin-eosin (H&E). During EF (6-78 hours post-hatching, HPH), mouth opening was observed at 72 HPH, with 44.2% yolk sac (YS) absorption, along with a linear digestive system and intestinal folds. At MF (96-144 HPE), YS absorption reached 68.1%, and hepatic and pancreatic differentiation and an increase in intestinal size were observed. During FF (168-342 HPE), YS absorption reached 93.6%, and barbel development was completed; the oesophageal mucosa presented a stratified squamous epithelium with abundant goblet cells, while glands and oxyntic cells were observed in the stomach, although their formation was slower compared to other organs. In conclusion, the development of the digestive system of E. mutisii was accelerated, except for the stomach, which showed a slower maturation process. These findings provide key information for determining optimal feeding times and designing balanced diets in captivity that contribute to the conservation of this species.